PENGARUH PEMBERIAN TEH TELUR TERHADAP LAMA PERSALINAN KALA 1 DI BPM “A” - Nina Fitri; Syahrifa Nur Aini (Universitas Fort de Kock Bukittinggi, 2021)
Prolonged labor is one of the causes of maternal death. The percentage of this case is 20% of all cases of causes of maternal death and 60% of cases of prolonged labor are inadequate. The inadequacy occurs because many women undergo an active phase for more than 6 hours and the cervical opening acceleration is less than 1 hour / cm. The purpose of this study was to determine The Effect of Egg Tea on the First Stage of Labor at BPM